Pengaruh Media Batik Jumputan Terhadap Kemampuan Motorik Halus Anak Usia 5–6 Tahun - Adila Dhiya Ulhaq; Asih Budi Kurniawati; Devi Nawangsasi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The problem addressed in this study is that the fine motor skills of children aged 5–6 years have not yet developed optimally. This study aims to determine the effect of jumputan batik on the fine motor skills of children aged 5–6 years. This study employs a quasi-experimental design with a quantitative approach. The research design employed was a one-group pretest-posttest design. The sampling technique used in this study was total sampling, with a sample size of 22 children. Data collection utilised an observational technique in the form of a checklist. Hypothesis testing employed the Wilcoxon test. The results indicate that the use of jumputan batik as a medium has an effect on children’s fine motor skills. This is evidenced by the results of the Wilcoxon test, which yielded a Z-value of -4.112 with an Asymp. Sig (2-tailed) of 0.000 < 0.05, thus accepting the alternative hypothesis (Ha). Children’s fine motor skills can be assessed based on the dimensions of muscle strength, grasping, object manipulation, hand stability, and eye-hand coordination.